Analyzing Tax Policies in Turkey and Indonesia: A Comparative Study for Improved Competitiveness and Neutrality - Yunia Amelia (Publication of the International Journal and Academic Research, 2024)
For many countries, taxes are the main source of revenue to finance all expenditures, including the promotion of economic growth. To compare the tax systems of different countries, the Organisation for Economic Co-operation and Development (OECD) has developed the International Tax Competitiveness Index (ITCI). This study examines Türkiye and Indonesia’s tax policies, focusing on their influence on economic competitiveness and tax neutrality. This study identifies the strengths and weaknesses of each country's tax system and provides recommendations for enhancing their competitiveness and neutrality. This study uses a comparative approach to analyse tax policies in Türkiye and Indonesia. The analysis reveals that a neutral tax code is crucial for economic growth and for attracting investment. Türkiye's tax system offers insights into efficient tax structures, with lower corporate tax rates and non-distortionary property taxes contributing to its higher ranking in the ITCI. Conversely, Indonesia's tax system presents opportunities for improvement by adopting similar practices. This study suggests that Indonesia could benefit from targeted tax incentives, better tax administration, and investment in tax education and training. Broadening the tax base and leveraging digital technologies for tax administration have been identified as key strategies to improve Indonesia's tax competitiveness. The study concludes that both Türkiye and Indonesia can enhance their tax systems by learning from each other and countries with high tax competitiveness rankings. By implementing the recommended measures, these countries can stimulate economic growth, investment, and achieve a more competitive and neutral tax